The 95% effective dose of nalbuphine in patient-controlled intravenous analgesia for patients undergoing laparoscopic total hysterectomy compared to equivalent sufentanil. Issue 22 (29th May 2020) - Sun, Zhentao; Zhu, Zefei; Yang, Guanyu; Zheng, Hongyu
Abstract: Purpose: To evaluate the 95% effective dose of nalbuphine in patient-controlled intravenous analgesia (PCIA) by the sequential method and compare the analgesia efficacy with the equivalent dose of sufentanil on patients undergoing laparoscopic total hysterectomy. Methods: In the first part, we defined a successful analgesia as the highest VAS ⩽3 in 24 hours postoperatively. On the contrary, a failed analgesia was the highest VAS>3. According to the last patient's outcome, the next patients would be given an increase or decreased dose grade. This process ended up with 9 cross-over points. In the second part, 60 patients undergoing laparoscopic total hysterectomy were selected. They were randomly divided into 2 groups (n = 30 each group): receiving sufentanil 1.78 μg/kg (group S) and nalbuphine 1.78 mg/kg (group N). PCIA pump was given at the end of the operation with 5 mL bonus loading. The total amount of PCIA was 100 mL and programmed to deliver 0.5 mL each time with a lockout interval of 15 minutes and the background infusion amount of 2 mL/h. The VAS score and Ramsay score of were collected after the operation, the number of effective pressing times of PCIA were also recorded. Adverse reactions were documented in detail. Results: The 95% effective dose of nalbuphine in PCIA on patients undergoing laparoscopic total hysterectomy was 1.78 mg/kg. There was no significant difference in VAS between the sufentanil group and the nalbuphine groups ( P > .05), but the number of the use of PCIA in the group S was more than that in the group N obviously ( P <.05). The group S has a lower ramsay sedation score than group N at every time point. ( P <.05). The incidence of nausea and vomiting was not statistically significant differences between two groups in the first 24 hours after colonoscopy ( P > q .05). Conclusion: Nalbuphine 1.78 mg/kg in PCIA is recommended for the patients undergoing laparoscopic total hysterectomy. And nalbuphine is a reasonable alternative to sufentanil when used in PCIA.